EACVI survey on hypertrophic cardiomyopathy. (27th December 2021) - Podlesnikar, Tomaz; Cardim, Nuno; Ajmone Marsan, Nina; D'Andrea, Antonello; Cameli, Matteo; Popescu, Bogdan A; Schulz-Menger, Jeanette; Stankovic, Ivan; Toplisek, Janez; Maurer, Gerald; Haugaa, Kristina H; Dweck, Marc R
Abstract: Aims: The European Association of Cardiovascular Imaging (EACVI) Scientific Initiatives Committee performed a global survey to evaluate current practice for the assessment and management of patients with hypertrophic cardiomyopathy (HCM). Methods and results: A total of 213 centres from 38 different countries (87% European) responded to the survey. One hundred twenty-one (57%) centres followed HCM patients in a general cardiology outpatient clinic and 85 (40%) centres in a specialized HCM/cardiomyopathy clinic. While echocardiography was the primary imaging modality, cardiovascular magnetic resonance (CMR) has become an important complementary tool. Cardiac anatomy, left ventricular (LV) systolic, and diastolic function were assessed according to current European guidelines and recommendations. To evaluate LV obstruction, 49% of the centres performed bedside provocation manoeuvres in every patient and 55% of the centres used exercise stress echocardiography. The majority of centres used the 5-year risk assessment of sudden cardiac death (SCD) calculated with the HCM Risk-SCD score. However, 34% of the centres also used extensive non-infarct late gadolinium enhancement on CMR and 27% the presence of LV apical aneurysm to help select patients for primary prevention implantable cardioverter-defibrillator therapy. Ninety-nine percent of the responding centres performed regular imaging follow-up of HCM patients. Conclusion: Most centres followed European guidelines and recommendations for the diagnosis and management of patients with HCM. The importance of bedside provocation manoeuvres and exercise stress echocardiography to diagnose LV outflow obstruction requires emphasis. Additional risk markers for SCD are used in many centres and might indicate the need for an update of current European recommendations.